2019
DOI: 10.1007/978-3-030-05429-8
|View full text |Cite
|
Sign up to set email alerts
|

Social Networks: Models of Information Influence, Control and Confrontation

Abstract: The series "Studies in Systems, Decision and Control" (SSDC) covers both new developments and advances, as well as the state of the art, in the various areas of broadly perceived systems, decision making and control-quickly, up to date and with a high quality. The intent is to cover the theory, applications, and perspectives on the state of the art and future developments relevant to systems, decision making, control, complex processes and related areas, as embedded in the fields of engineering, computer scien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
19
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(21 citation statements)
references
References 0 publications
0
19
0
2
Order By: Relevance
“…The models of finding a consensus are close to the models of informational influence on population and information control models (see, e.g., papers [2,3] and books [4,5]). A model of opinion dynamics with two principals or centers of influence is presented in [6], in which the conditions of existence of the limit opinions are obtained for a given matrix of influences.…”
Section: Introductionmentioning
confidence: 62%
“…The models of finding a consensus are close to the models of informational influence on population and information control models (see, e.g., papers [2,3] and books [4,5]). A model of opinion dynamics with two principals or centers of influence is presented in [6], in which the conditions of existence of the limit opinions are obtained for a given matrix of influences.…”
Section: Introductionmentioning
confidence: 62%
“…A detailed analysis of influence models and some formulations of control models were given in the monograph [25]. A closest approach to the one developed below was presented in [26,27], where linear-quadratic game-theoretic models were constructed and investigated on a network with two influence nodes.…”
Section: Introductionmentioning
confidence: 99%
“…The reviews can be found in [3]- [4]. Along with the models of influence, there are also models of opinion control in social networks [6]. In this case there are one or several external control agents that exert influence on the opinions of basic network agents in their interests.…”
mentioning
confidence: 99%
“…Formally, the strong subgroups are the strong components of a network which belong to the vertex base of its condensation [13]. Thus, the first stage of analysis of a network consists in its segmentation on strong subgroups and satellites [6] as well as calculation of additional quantitative characteristics of the members of strong subgroups [2]. In the second stage the problems of optimal and conflict (game theoretic) opinion control are solved.…”
mentioning
confidence: 99%